DEVELOPMENT OF TEACHING MATERIALS TO IMPROVE READING COMPREHENSION SKILLS FOR 5TH GRADE STUDENTS: CANVA APP SUPPORTED - Puspita, Ryan Dwi; Wardani, Duhita Savira; Rabbani, Sylvia (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
The purpose of this study was to examine the effect of teaching materials based on the Canva application developed on improving the reading comprehension skills of grade 5 students. The approach used in this study was Design and Development (Ellis & Levy, 2010) with six steps, namely Identify the Problem, Describe the Objectives, Design & Develop the Artifact, Test the Artifact and Evaluate the Testing Result, Communicating the Testing Result and Dissemination. Data were collected through teacher interviews, questionnaires, pre-test and post-test. This study used a sample of 171 5th grade students in 3 elementary schools. The results of this study indicate that the use of teaching materials based on the Canva application has a significant effect on increasing the ability to read comprehension of information texts for grade 5 students. This is evidenced by the differences in students' reading comprehension abilities of information texts before and after learning by using application-based teaching materials. canva. This research has implications for the ease of teachers in achieving learning objectives with the support of teaching materials, media, worksheets and interesting and practical activities that are able to stimulate students in improving their reading comprehension skills, especially informational texts.